Ideological Representation in the Short Story Collection Corat-coret di Toilet by Eka Kurniawan: Gramsci's Hegemony Analysis - Anggraeni, Astri; Fatimah, Ade Fitria; Darmawan, Auranita Gibrani (Politeknik Siber Cerdika Internasional, 2025)
This article explores ideological representation in Eka Kurniawan’s short story collection Corat-coret di Toilet using Antonio Gramsci’s theory of hegemony. The study aims to examine how dominant and subaltern ideologies are contested and negotiated within the selected stories. Employing a qualitative descriptive method, the research focuses on four short stories that exhibit significant ideological formations: